Analysis of load-sharing characteristics of herringbone gear transmission system considering symmetry error - Yiping Zhou; Heyun Bao; Zouhao Song; Zhizhong Zhang; Fengxia Lu (Industrial Lubrication and Tribology, 2026)
Purpose The symmetry error affects the load-sharing performance of herringbone gear transmission systems. This paper aims to investigate the influence of symmetry error on the load-sharing characteristics of herringbone gear systems. Design/methodology/approach Based on the lumped mass method, the time-varying meshing stiffness and symmetry error are introduced to establish a dynamic model of herringbone gear bending-torsion-shaft coupling, and the load-sharing performance test is carried out on the herringbone gear test bench to verify the correctness of the theoretical analysis. Findings The greater the symmetry error, the larger the load distribution coefficient, the more obvious the eccentric load of the system. And the error of the experimental results and theoretical results is 15.01%, the larger the load, the better the load-sharing performance, which verifies the consistency between the test results and the theoretical analysis. Originality/value The research results provide reference value for the load-sharing characteristics of herringbone gears with symmetry error. Peer review The peer review history for this article is available at: https://publons.com/publon/10.1108/ILT-03-2025-0125/